2015
DOI: 10.3390/healthcare3030695
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Resistance Training on Physical Function and Quality of Life in Breast Cancer Survivors

Abstract: Breast cancer survivors (BCS) exhibit decreased physical function and quality of life (QOL) following cancer treatments. Resistance training (RT) may elicit positive changes in physical and mental well-being. This study assessed 27 BCS, pre-and post-intervention (six months) on the following variables: muscular strength (via one repetition maximum (1RM) of chest press and leg extension), physical function (via the Continuous Scale-Physical Functional Performance test) and QOL (via the Short Form-36 survey). RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…The BMI was not correlated with the ratio to the predicted 6MWT. It is thought that the weight of breast cancer patients within 1 year after surgery is not influenced by a reduction in aerobic clearly as in other studies (Brown et al, 2015;Simonavice et al, 2015;Wirtz & Baumann, 2018). Fatness and decreased physical activity are known to be associated with mortality and recurrence of breast cancer (de Boer, Wörner, Verlaan, & Leeuwen, 2017).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…The BMI was not correlated with the ratio to the predicted 6MWT. It is thought that the weight of breast cancer patients within 1 year after surgery is not influenced by a reduction in aerobic clearly as in other studies (Brown et al, 2015;Simonavice et al, 2015;Wirtz & Baumann, 2018). Fatness and decreased physical activity are known to be associated with mortality and recurrence of breast cancer (de Boer, Wörner, Verlaan, & Leeuwen, 2017).…”
Section: Discussionmentioning
confidence: 82%
“…It has been shown that arm impairments such as flexibility, strength and oedema are present in breast cancer patients within 1 year after surgery, but it does not affect overall QOL, physical activity and fatness. However, even if it does not affect overall QOL, physical activity and fatness, it would be necessary to provide appropriate intervention because there were groups with impairment clearly as in other studies (Brown et al, ; Simonavice et al, ; Wirtz & Baumann, ). Fatness and decreased physical activity are known to be associated with mortality and recurrence of breast cancer (de Boer, Wörner, Verlaan, & Leeuwen, ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Likewise, cancer-related fatigue is a subjective sense of exhaustion not relieved by rest that, also, reduces overall functionality and physical performance [12,24,36], which can play a significant role on exacerbating the loss of muscle tissue commonly observed in cancer survivors [4]. Physical exercise interventions, such as strength training, have been proposed to improve muscle function, attenuating cancer-related fatigue and cancer-induced muscle wasting [17,31,32,38]. However, to assess the effect of training interventions, it is important to use reliable measurements to meaningfully detect changes, if indeed these changes have been promoted by training and not by motor learning from repeating testing [19].…”
Section: Discussionmentioning
confidence: 99%